Optimization of wet sliding wear parameters of Titanium grade 2 and grade 5 bioimplant materials for orthopedic application using Taguchi method - Solanke, S G; Gaval, V R (Journal of Metals, Materials and Minerals, 2020)
In this research ball on disc wear tests have been carried out on Titanium grade 2 and Titanium grade 5 material using ASTM G-99 standard at room temperature in simulated body fluid. The tribological property such as the weight loss was studied by using the Taguchi design of experiments. The design of experiment was done using an L18 orthogonal array. An analysis of variance demonstrated that the individual contribution such as the applied normal load factor was 91.17% for weight loss, which means it is highest individual contribution as compared to other factors so it was concluded that weight loss is mainly influenced by the applied normal load. The analysis of the signal to noise ratio shows that the optimal weight loss was obtained with titanium grade 5 material at an applied normal load of 5 N with sliding velocity 0.05 m/s for sliding distance of 100 m. The results showed that weight loss increases with increasing the applied normal load and sliding velocity. The microstructure of all substrate materials was analyzed using a scanning electron microscope. Wear track study showed that adhesive dominant wear mechanism for both the grades.